Doxological (Im)Purity? Nicholas of Cusa’s ‘Art of Praising’ and Liturgical Thinking in 21st Century - Inigo Bocken (Religions, 2022)
It is noteworthy that the thinking of Nicholas of Cusa (1401–1464) has recurred again and again among prominent recent theologians who, critical of Modern rationality, have brought back to the fore the importance of liturgical praxis. Often, however, the mystical theology of Nicholas of Cusa had been presented during the Twentieth Century primarily as an unfinished precursor to Modern subject-philosophy in the line of Kant. In this contribution, I will consider this striking change of perspective against the background of recent debates concerning the role of liturgy not only for theology, but also for philosophy. Does Cusa’s ‘art of praising’ offer a way out of the dilemmas facing liturgical thought?